Whole-genomic analysis of G3P[23], G9P[23] and G3P[13] rotavirus strains isolated from piglets with diarrhea in Thailand, 2006-2008 - Shoko Okitsu (2018)
Group A rotavirus (RVA) is the most common cause of severe acute viral gastroenteritis in humans and animals worldwide. This study characterized the whole genome sequences of porcine RVAs, 2 G3P[23] strains (CMP40/08 and CMP48/08), 1 G9P[23] strain (CMP45/08), and 1 G3P[13] strain (CMP29/08). These strains were collected from diarrheic piglets less than 7. weeks of age in 4 pig farms in Chiang Mai, Thailand, in 2008. The VP7-VP4-VP6-VP1-VP2-VP3-NSP1-NSP2-NSP3-NSP4-NSP5 genes of CMP40/08 and CMP48/08 strains were assigned as G3-P[23] -I5-R1-C1-M1-A8-N1-T1-E1-H1 genotypes based on their nucleotide sequences and phylogenetic analyses. The CMP29/08 strain was different from the CMP40/08 and CMP48/08 strains only in the VP4 gene, since it was assigned as P[13] genotype. Furthermore, the VP7 gene of the CMP45/08 strain was classified as genotype G9, and the NSP3 gene as T7 genotype. The finding of this study supports the porcine-origin of T7 genotype, although the NSP3 gene of this strain was similar to the bovine UK strain at the highest nucleotide sequence identity of 92.6%. Whole genome sequence analysis of the porcine RVAs indicated that multiple inter-genotypic and intra-genotypic reassortment events had occurred among the porcine RVAs circulating in this studied area. Interestingly, the VP7 gene of the CMP45/08 strain, and the VP1, NSP2, and NSP4 genes of all four porcine RVAs strains described in this study revealed much similarity to those of two porcine-like human RVA strains (RVA/Human-tc/THA/Mc323/1989/G9P[19] and RVA/Human-tc/THA/Mc345/1989/G9P[19]) detected in Thailand in 1989. The present study provided important information on the evolution of porcine RVA. © 2013 Elsevier B.V.